Um banquete nos tempos líquidos: o amor e a amizade no romance Os Íntimos, de Inês Pedrosa - Pereira, Helitânia dos Santos (2014)
This study makes a reading about love and friendship representations on the novel The intimate, by the contemporany portuguese writer Inês Pedrosa. The work portrays the friendship between five men who meet to talk about several topics, especially love. This configuration of the novel’s scene recalls the classic work of Plato, The Banquet, the first and greatest treatise about the love’s nature. It is intended to show how the literary representations of the work in question are in line with the present concepts in the so called liquid modernity. For this analysis, was taken a theoretical approach of the modern society trends from the Zigmunt Bauman’s theory, as well as a historical path about conceptions of love (May and Branden), friendship (Aristotle and Cicero) and masculinity (Courtine, Corbin, Vigarello, Oliveira and Nolasco) in the sense to better understand the transformations that are felt in current times (Paz, Zeldin, Giddens). Necessary to draw attention to the polyphony of announcer voices of the novel and this relates the fact that modernity is a stage where live side by side disparate conceptions.